2015
DOI: 10.3238/arztebl.2015.0605
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Prostate Cancer

Abstract: MRI/TRUS fusion-assisted targeted biopsy improves the detection rate of prostate cancer after a previous negative biopsy. Targeted biopsy is more likely to reveal clinically significant cancer than systematic biopsy; nevertheless, systematic biopsy should still be performed, even if the MRI findings are negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…found a clinically significant CDR of 37.5% in men with elevated PSA using 12-core systemic biopsy which is approximate to sensitivity data obtained in similar studies. 23,24…”
Section: Types Of Prostate Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…found a clinically significant CDR of 37.5% in men with elevated PSA using 12-core systemic biopsy which is approximate to sensitivity data obtained in similar studies. 23,24…”
Section: Types Of Prostate Biopsymentioning
confidence: 99%
“…6,22 Brock et al found a clinically significant CDR of 37.5% in men with elevated PSA using 12-core systemic biopsy which is approximate to sensitivity data obtained in similar studies. 23,24 Contemporary MRI-guided biopsy strategies preferentially detect clinically important lesions and offer clear benefits over the traditional systematic biopsy. 25 MRI-guided biopsy involves selective sampling of lesions identified as suspicious on mpMRI.…”
Section: Types Of Prostate Biopsymentioning
confidence: 99%
“…With the aid of MRI one can not only identify and localize, for example, cysts or calcifications of the male adnexa, but also often differentiate between recent and older bleeding. Moreover, there are clear indications that MRI may be helpful in detecting prostate cancer (31).…”
Section: Imagingmentioning
confidence: 99%
“…The actual ability of the transrectal ultrasound to detect prostate cancer itself is limited, with a sensitivity of about 73.6% and a specificity of 61.3%. Thus, the diagnostic accuracy of prostate biopsies varies with the imaging techniques used [8]. The TRUS prostate biopsy, however, has been demonstrated to have a high specificity of 96% but a sensitivity of only 48% [9].…”
Section: Introductionmentioning
confidence: 99%